Electra and Female Oedipus: Constitution of the subject from psychoanalysis - Morales, Monica (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2021)
As happens in any discipline that is disclosed, it does not take long for common sense notions to appear on the scene that infiltrates in a simplification effort. This es the case of the so-called “Electra complex in psychoanalysis so widespread even in the Royal Spanish Academy (RAE) the purpose of this writing is to examine the proposals mainly of Sigmund Freud and Jacques Lacan who elaborate theoretical-clinical assumptions about female Oedipus, outlining its role in the psychic structuring of woman, and to unravel the magnificent character of Electra in its psychological-literary essence.